1995
DOI: 10.1037/0033-2909.117.3.416
|View full text |Cite
|
Sign up to set email alerts
|

Vocational rehabilitation of drug abusers.

Abstract: Employment has been identified as an important element in the rehabilitation of drug abusers and, together with abstinence from illicit drugs and criminal involvement, is frequently used as a criterion of treatment outcome. The research literature for the last 20 years on variables affecting employment and the vocational rehabilitation of drug abusers is reviewed with an emphasis on (a) the identification of variables influencing the employment of drug abusers and (b) the evaluation results of interventions th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
181
0
8

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(197 citation statements)
references
References 92 publications
(188 reference statements)
8
181
0
8
Order By: Relevance
“…This is supported by Dean's (2003) assessment of people with multiple problems, as well as Platt's (1995) review of research which found that the types of programme that achieved some success involved supported work, job-seeking and placement and personal competency and skill-building. Similarly, Sutton and colleagues' (2004) review of employment support programmes identified ongoing support for drug users, especially with regard to tackling relapse and the ability to refer to other support services, as crucial to success .…”
Section: Discussionmentioning
confidence: 97%
“…This is supported by Dean's (2003) assessment of people with multiple problems, as well as Platt's (1995) review of research which found that the types of programme that achieved some success involved supported work, job-seeking and placement and personal competency and skill-building. Similarly, Sutton and colleagues' (2004) review of employment support programmes identified ongoing support for drug users, especially with regard to tackling relapse and the ability to refer to other support services, as crucial to success .…”
Section: Discussionmentioning
confidence: 97%
“…Esto se debe a varias y diversas razones: discriminación, antecedentes criminales, problemas de salud, falta de habilidades y de formación profesional, entre otras 44 . La integración a la vida laboral se ha mostrado asociada a mejores resultados en el tratamiento con metadona para éstos pacientes 47,48 , y viceversa, por ejemplo la permanencia en los TM se asocia a una mayor integración laboral 28 . La reinserción laboral, o la posibilidad de conservar el trabajo, son un aspecto fundamental en la mejora de la calidad de vida de éstos pacientes, y las intervenciones en ese sentido en el marco de los TM deben ser reforzadas.…”
Section: Discussionunclassified
“…Indirect evidence suggests that the likelihood of having service-connection benefits reduced appears to be low but the odds are in fact unknown (Sayer, Spoont, & Nelson, 2004). Employment is an important component in the rehabilitation of drug users (e.g., Platt, 1995;Comerford, 1999) and, thus, unemployment and underemployment pose a barrier to recovery for Veterans with substance use problems.…”
Section: Discussionmentioning
confidence: 99%